Non-governmental organizations’ collaboration with local entities and their potential for implementing social innovations - Katarzyna Zajda (ACTA INNOVATIONS, 2017)
Non-governmental organizations encounter some barriers when trying to implement social innovations, such as having limited ability to collaborate with other entities designed to solve social problems or limiting that collaboration to entities which are not interested in implementing such innovations. The aim of this article is to characterize the collaboration between non-governmental organizations from Lubelskie Province and local entities, as well as to evaluate the collaboration in terms of the possibility of implementing social innovations. The study was carried out between October and December 2016 and was based on the following research questions: 1. What kind of social problems do the investigated non-governmental organizations from the rural communes of Lubelskie Province try to solve? 2. What entities are involved in solving those problems? 3. Do the investigated organizations often collaborate with them? 4. Should the collaboration be modified or changed? 5. What entities should increase their participation in the cooperation network? The study involved 108 chairpersons of non-governmental organizations from the rural communes of Lubelskie Province, with whom in-depth interviews with a standardized list of targeted information were carried out. The article presents part of the collected empirical material. Although non-governmental organizations are willing to engage in non-standard, unconventional or atypical projects, they limit their activity to problems regarded as “easier to solve” or to activities that are not likely to solve those problems. In this context, extending nongovernmental organizations' cooperation networks by new local non-governmental organizations (out of the social welfare field) does not seem as desirable as their further collaboration with public sector organizations based on the principle of partnership and oriented at implementing social innovations.